Femtosecond laser strengthening method for improving surface integrity of laser cladding high-temperature alloy

The surface of the high-temperature alloy after laser cladding is processed by femtosecond laser enhancement method, which solves the surface defect problem, improves the surface integrity and the service life of the components, and enhances the fatigue and wear resistance.

CN119571314APending Publication Date: 2025-03-07XIAN LASER TRANSMISSION TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411828735.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Laser cladding technology has defects such as pores and unfusion zones in the surface treatment of high-temperature alloys, which affects surface integrity and long-term stability.

Method used

The femtosecond laser enhancement method is used to surface strengthen the surface of the high-temperature alloy after laser cladding to remove cracks and pores, and the optimal beam quality and energy density are obtained by adjusting the output power, pulse width and repetition frequency of the femtosecond laser.

Benefits of technology

It significantly improves the integrity of the surface of high-temperature alloy, extends the service life of the components, enhances fatigue resistance and wear resistance, and improves service performance and reliability in aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571314A_ABST
    Figure CN119571314A_ABST
Patent Text Reader

Abstract

The invention discloses a femtosecond laser strengthening method for improving the surface integrity of a laser cladding high-temperature alloy, and belongs to the technical field of laser cladding postprocessing, and the femtosecond laser strengthening method comprises the following steps: S1, selecting a proper high-temperature alloy as a base material, and cleaning and pretreating the surface of the base material; s2, a cladding laser is started to clad the base material; S3, a femtosecond laser system is set, and the optimal light beam quality and energy density are obtained; according to the method, the cladding surface is strengthened through femtosecond laser, the defects of cracks, air holes and the like appearing on the material surface after laser cladding are effectively removed, the surface integrity is greatly improved, premature failure caused by the problems of stress concentration and the like in the using process of components can be prevented through elimination of the surface defects, the service life of the components is prolonged, and the production cost is reduced. The safety and stability of the key hot end component are guaranteed, and the surface integrity of the high-temperature alloy component can improve the service performance and reliability under extreme loads such as high temperature, high flow speed and high pressure in the fields of aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser cladding post-processing, and in particular relates to a femtosecond laser strengthening method for improving the surface integrity of a laser cladding high-temperature alloy. Background Art

[0002] High-temperature alloys play an indispensable role in the manufacturing of key hot-end components in the aerospace field due to their excellent high-temperature strength, good oxidation resistance, thermal corrosion resistance and fatigue resistance. In the actual service process, these components are subjected to extreme loads such as high temperature, high flow rate and high pressure, and are prone to damage. In order to solve the above problems and extend the service life of components, laser cladding technology is widely used in such scenarios as an advanced surface treatment and repair method. This technology uses a high-energy-density laser beam to quickly heat the surface of the workpiece to a molten state, and then re-solidifies it through a subsequent natural cooling process, thereby forming one or more new protective layers on the original substrate. According to needs, metal materials that are the same or different from the substrate can be selected as cladding materials to achieve the purpose of improving specific properties. The coating prepared by laser cladding technology is not only dense and uniform in structure, but also can achieve a strong metallurgical bond with the substrate material, greatly improving the bonding strength at the interface. At the same time, due to the characteristics of rapid solidification, it can also effectively refine the grain size and enhance the overall mechanical properties; in addition, the whole process has little effect on the parent material, so it is also conducive to maintaining the original shape and dimensional accuracy of the parts.

[0003] However, at the current stage, laser cladding technology still has some limitations that need to be overcome. The most prominent of these is how to ensure that the quality of the final surface meets high standards. For example, defects such as pores and unfused areas may appear during actual operation, which will affect the overall integrity of the coating and its long-term stability.

[0004] In order to avoid the above technical problems, it is necessary to provide a femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloys to overcome the above defects in the prior art. Summary of the invention

[0005] The object of the present invention is to provide a femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloys, so as to solve the problems raised in the above-mentioned background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloy, comprising the following steps:

[0007] S1. Select a suitable high-temperature alloy as the substrate and clean and pretreat the substrate surface;

[0008] S2, start the cladding laser to clad the substrate:

[0009] S3, setting up the femtosecond laser system to obtain the best beam quality and energy density;

[0010] S4, using femtosecond laser to strengthen the cladding surface and remove cracks and pores on the surface of the material after laser cladding;

[0011] S5. Microstructure analysis, hardness test, and residual stress test were performed on the cladding samples and the femtosecond laser strengthened samples after cladding to evaluate the surface integrity of the coating.

[0012] As a preferred embodiment, the high-temperature alloy is a high-temperature alloy used in the manufacture of key hot end components in the aerospace field, and has excellent high-temperature strength, good oxidation resistance, hot corrosion resistance and fatigue resistance.

[0013] As a preferred embodiment, the cleaning and pretreatment of the substrate surface includes removing oil stains, impurities and oxide layers on the substrate surface.

[0014] As a preferred embodiment, the cladding laser is started to clad the substrate, by placing a coating material on the surface of the substrate, starting the cladding laser, and cladding according to a preset scanning path and speed. The preset scanning path and speed determine the scanning path according to the substrate shape, the cladding area requirements, and the thickness uniformity requirements of the cladding layer, and the scanning speed is adjusted according to the characteristics of the cladding material and the required cladding layer performance combined with the laser power number.

[0015] As a preferred embodiment, during the laser cladding process, the parameters of the cladding laser are set according to the coating material and the characteristics of the substrate.

[0016] As a preferred embodiment, the femtosecond laser system is set up to obtain optimal beam quality and energy density by adjusting the output power, pulse width and repetition frequency of the femtosecond laser, and the focal length of the focusing lens.

[0017] As a preferred implementation scheme, the surface of the cladding is strengthened by using a femtosecond laser to remove cracks and pores on the surface of the material after laser cladding. The pulse width of the femtosecond laser is an ultrashort pulse width to ensure that the heat affected area is extremely small.

[0018] As a preferred embodiment, the microstructure analysis uses an electron microscope to observe the interface between the cladding layer and the substrate and the changes in the grain structure; the hardness test uses a Vickers microhardness tester to measure the surface microhardness; and the residual stress test uses an X-ray diffraction non-destructive testing method to detect the surface residual stress.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention strengthens the cladding surface through femtosecond laser, effectively removes defects such as cracks and pores that appear on the material surface after laser cladding, and greatly improves the surface integrity. The elimination of surface defects can prevent the components from failing prematurely due to problems such as stress concentration during use, thereby extending the service life of the components and ensuring the safety and stability of key hot-end components. The surface integrity of high-temperature alloy components can improve the service performance and reliability of aerospace and other fields under extreme loads such as high temperature, high flow rate, and high pressure.

[0021] In the present invention, after femtosecond laser strengthening, the surface roughness of the cladding sample is significantly improved, which is not only beneficial to improving the appearance quality of the parts, but more importantly, the lower surface roughness can reduce friction resistance, reduce the energy loss of the parts during operation, and improve the working efficiency of the parts. At the same time, it also helps to improve its corrosion resistance, because the rough surface is more likely to accumulate corrosive media.

[0022] According to the present invention, the microhardness of the surface of the high-temperature alloy is improved after cladding, and the improvement of the hardness enhances the wear resistance of the component. When the high-temperature alloy component is working, it often faces wear problems. The higher microhardness can effectively resist wear, reduce material loss, and maintain the dimensional accuracy and shape accuracy of the component, thereby maintaining the stable performance of the component and further improving the durability of the component.

[0023] The present invention causes plastic deformation on the surface of the high-temperature alloy through femtosecond laser strengthening, thereby introducing residual compressive stress. The residual compressive stress can effectively offset part of the tensile stress borne by the component during operation, thereby significantly improving the fatigue resistance of the component. In the fields of aerospace, components are often subjected to cyclic loads. Improving fatigue resistance is crucial to preventing the generation and expansion of fatigue cracks in the components, which can greatly reduce the risk of failure of the components due to fatigue damage and improve the overall reliability and service life of the components. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic diagram of the overall process of the femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloys according to the present invention;

[0025] Figure 2 It is a schematic diagram of the surface roughness of the sample after cladding and the sample strengthened by femtosecond laser after cladding according to the present invention;

[0026] Figure 3 It is a schematic diagram of the surface residual stress distribution of the sample after cladding and the sample strengthened by femtosecond laser after cladding according to the present invention;

[0027] Figure 4It is a schematic diagram of the surface microhardness distribution of the sample after cladding and the femtosecond laser strengthened sample after cladding of the present invention. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with the embodiments.

[0029] The following examples are used to illustrate the present invention, but they cannot be used to limit the scope of protection of the present invention. The conditions in the examples can be further adjusted according to specific conditions. Simple improvements to the method of the present invention under the premise of the concept of the present invention belong to the scope of protection claimed in the present invention.

[0030] See also Figure 1-4 The present invention provides a femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloy, comprising the following steps:

[0031] S1. Select a suitable high-temperature alloy as the substrate and clean and pretreat the substrate surface;

[0032] S2, start the cladding laser to clad the substrate:

[0033] S3, setting up the femtosecond laser system to obtain the best beam quality and energy density;

[0034] S4, using femtosecond laser to strengthen the cladding surface and remove cracks and pores on the surface of the material after laser cladding;

[0035] S5. Microstructure analysis, hardness test, and residual stress test were performed on the cladding samples and the femtosecond laser strengthened samples after cladding to evaluate the surface integrity of the coating.

[0036] By strengthening the cladding surface through femtosecond laser, defects such as cracks and pores on the material surface after laser cladding are effectively removed, greatly improving the surface integrity. The elimination of surface defects can prevent the components from failing prematurely due to stress concentration and other problems during use, extending the service life of the components and ensuring the safety and stability of key hot end components. The surface integrity of high-temperature alloy components can improve the service performance and reliability under extreme loads such as high temperature, high flow rate, and high pressure in aerospace and other fields.

[0037] High-temperature alloys are high-temperature alloys used in the manufacture of key hot-end components in the aerospace field. They have excellent high-temperature strength, good oxidation resistance, hot corrosion resistance and fatigue resistance.

[0038] Cleaning and pre-treating the substrate surface includes removing oil, impurities and oxide layers from the substrate surface.

[0039] The surface oil is removed by wiping or soaking the substrate surface with an organic solvent. The organic solvent can dissolve the oil and separate it from the substrate surface, and then wipe or wash it off. Physical methods such as blowing, wiping or washing can be used to remove dust, particles and other impurities on the substrate surface. Compressed air can be used to blow the substrate surface to blow away loose impurities, or a clean soft brush can be used to gently brush off surface impurities. For impurities that are difficult to remove, an appropriate cleaning solution can be used for cleaning, such as cleaning with a weak alkaline solution and then rinsing with clean water to ensure that the substrate surface is clean. The oxide layer is removed by chemical or mechanical methods. Chemical methods such as pickling, select a suitable acid solution to soak the substrate surface for a certain period of time, so that the oxide layer reacts chemically with the acid and is dissolved and removed, and then rinsed with clean water and dried. Mechanical methods can be sandpaper polishing, sandblasting, etc. The oxide layer is removed by the mechanical action of polishing or sandblasting, but attention should be paid to controlling the intensity and particle size of polishing or sandblasting to avoid excessive damage to the substrate, while ensuring surface flatness and finish to facilitate subsequent laser cladding and femtosecond laser strengthening treatment.

[0040] The cladding laser is started to clad the substrate. The coating material is placed on the surface of the substrate, and the cladding laser is started to perform cladding according to the preset scanning path and speed. The preset scanning path and speed are determined by the substrate shape, the cladding area requirements and the thickness uniformity requirements of the cladding layer. The scanning speed is adjusted by the cladding material characteristics and the required cladding layer performance combined with the laser power number.

[0041] During the laser cladding process, the parameters of the cladding laser are set according to the coating material and substrate characteristics.

[0042] The femtosecond laser system is set up to obtain the best beam quality and energy density. The output power, pulse width and repetition frequency of the femtosecond laser, as well as the focal length of the focusing lens are adjusted to obtain the best beam quality and energy density. The output power, pulse width and repetition frequency of the femtosecond laser, as well as the focal length of the focusing lens are adjusted according to the surface condition after cladding and the required strengthening effect, so that the femtosecond laser can effectively remove defects and optimize surface properties when acting on the cladding surface.

[0043] After cladding, the microhardness of the high-temperature alloy surface is improved. The increase in hardness enhances the wear resistance of the components. When high-temperature alloy components are working, they often face wear problems. Higher microhardness can effectively resist wear, reduce material loss, and maintain the dimensional accuracy and shape accuracy of the components, thereby maintaining the stability of the performance of the components and further improving the durability of the components.

[0044] Femtosecond laser is used to strengthen the cladding surface and remove cracks and pores on the surface of the material after laser cladding. The pulse width of the femtosecond laser is ultra-short, which ensures that the heat-affected zone is extremely small, thereby avoiding additional thermal damage to the cladding layer and substrate.

[0045] Through femtosecond laser strengthening, the surface of the high-temperature alloy undergoes plastic deformation and residual compressive stress is introduced. The residual compressive stress can effectively offset part of the tensile stress borne by the component during operation, thereby significantly improving the fatigue resistance of the component. In fields such as aerospace, components are often subjected to cyclic loads. Improving fatigue resistance is crucial to preventing the generation and expansion of fatigue cracks in components. It can greatly reduce the risk of failure of components due to fatigue damage and improve the overall reliability and service life of components. After femtosecond laser strengthening, the surface roughness of the cladding sample is significantly improved, which is not only beneficial to improving the appearance quality of the component, but more importantly, lower surface roughness can reduce friction resistance, reduce energy loss of components during operation, and improve the working efficiency of components. It also helps to improve its corrosion resistance because rough surfaces are more likely to accumulate corrosive media.

[0046] The microstructure analysis uses an electron microscope to observe the interface between the cladding layer and the substrate and the changes in the grain structure; the hardness test uses a Vickers microhardness tester to measure the surface microhardness; the residual stress test uses an X-ray diffraction non-destructive testing method to detect the surface residual stress.

[0047] Example:

[0048] A digital video microscope was used to characterize the surface profile of the high-temperature alloy before and after femtosecond laser strengthening. The roughness test system provided by the equipment was used to measure the linear roughness of the sample surface along the long axis direction. The roughness test was performed five times to obtain the average value and calculate the error. The test results are shown in Figure 2. Figure 2 As shown in the figure, the surface roughness of the cladding sample is 11.05μm, and the surface roughness of the femtosecond laser strengthened sample after cladding is 2.13μm, indicating that the femtosecond laser greatly improves the surface roughness of the high-temperature alloy laser cladding.

[0049] The residual stress test was conducted according to HB 20116-2012, using the X-ray diffraction nondestructive testing method. The high-pressure impact target material was Mn target, the diffraction angle was 152°, and the diffraction spot diameter was 2 mm. The test results are shown in Figure 3As shown in the figure, the residual stress on the surface of the cladding sample is 51.12MPa, and the residual stress on the surface of the femtosecond laser strengthened sample after cladding is -195.6MPa. This is because when the femtosecond laser irradiates the metal surface, in addition to causing temperature changes, compression waves are also generated inside the material. The propagation of these compression waves will cause plastic deformation of the surface layer of the material, while the lower layer remains in a relatively elastic state. As the laser pulse ends, the plastic deformation area of ​​the surface layer tries to return to its original state, but due to the limitation of the elastic part of the lower layer, a stable residual compressive stress field is eventually formed.

[0050] The microhardness of the cladding sample surface after femtosecond laser strengthening treatment was measured using a Vickers microhardness tester. The indentation load was 200 g and the dwell time was 15 s. During the surface microhardness test, multiple measurement points were randomly selected on the surface of the sample to obtain as comprehensive hardness distribution information as possible. The test results are shown in Figure 2. Figure 4 As shown in the figure, the surface microhardness of the cladding sample is 420.51HV, and the surface microhardness of the femtosecond laser strengthened sample after cladding is 450.95HV. This is because the femtosecond laser pulse has extremely high peak power and extremely short action time, which enables the laser energy to be quickly absorbed by the metal surface and converted into heat energy, causing the local area to instantly heat up to the melting point or even above the boiling point. Subsequently, due to the good thermal conductivity of the metal, the heat will be quickly conducted to the surrounding area, causing the area acted by the laser to undergo a rapid cooling process from high temperature to low temperature in a short period of time. This rapid heating and cooling rate far exceeds the conventional heat treatment method, and can form a very fine and evenly distributed grain structure, that is, nanocrystalline or ultrafine crystalline structure, thereby improving the hardness of the material.

[0051] The working principle and use process of the present invention are as follows: first, a suitable high-temperature alloy is selected as the substrate, and a suitable coating material is selected according to the required performance, the substrate surface is cleaned and pretreated to ensure good coating adhesion, the substrate is laser clad, the coating material is placed on the substrate surface, the cladding laser is started, and cladding is performed according to a preset scanning path and speed, and then the femtosecond laser system is set up, the output power, pulse width and repetition frequency of the femtosecond laser, and the focal length of the focusing lens are adjusted to obtain the best beam quality and energy density, and then the femtosecond laser is used to strengthen the cladding surface. Due to the ultra-short pulse width of the femtosecond laser, the heat-affected zone is extremely small, and cracks and pores on the material surface after laser cladding can be removed, and finally, microstructure analysis, hardness test, residual stress test, etc. are performed on the cladding sample and the femtosecond laser-strengthened sample after cladding to evaluate the surface integrity of the coating.

[0052] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloy, characterized in that: The following steps are involved: S1. Select a suitable high-temperature alloy as the substrate and clean and pretreat the substrate surface; S2, start the cladding laser to clad the substrate: S3, setting up the femtosecond laser system to obtain the best beam quality and energy density; S4, using femtosecond laser to strengthen the cladding surface and remove cracks and pores on the surface of the material after laser cladding; S5. Microstructure analysis, hardness test, and residual stress test were performed on the cladding samples and the femtosecond laser strengthened samples after cladding to evaluate the surface integrity of the coating.

2. The femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloy according to claim 1, characterized in that: The high-temperature alloy is a high-temperature alloy used in the manufacture of key hot end components in the aerospace field, and has excellent high-temperature strength, good oxidation resistance, hot corrosion resistance and fatigue resistance.

3. The femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloy according to claim 1, characterized in that: The cleaning and pretreatment of the substrate surface includes removing oil stains, impurities and oxide layers on the substrate surface.

4. The femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloy according to claim 1, characterized in that: The cladding laser is started to clad the substrate, and the coating material is placed on the surface of the substrate, and the cladding laser is started to perform cladding according to a preset scanning path and speed. The preset scanning path and speed determine the scanning path according to the substrate shape, the cladding area requirements and the thickness uniformity requirements of the cladding layer, and the scanning speed is adjusted according to the cladding material characteristics and the required cladding layer performance combined with the laser power number.

5. The femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloy according to claim 1, characterized in that: During the laser cladding process, the parameters of the cladding laser are set according to the coating material and the characteristics of the substrate.

6. The femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloy according to claim 1, characterized in that: The femtosecond laser system is set up to obtain optimal beam quality and energy density by adjusting the output power, pulse width and repetition frequency of the femtosecond laser, and the focal length of the focusing lens.

7. The femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloy according to claim 1, characterized in that: The femtosecond laser is used to strengthen the cladding surface, and cracks and pores appearing on the surface of the material after laser cladding are removed. The pulse width of the femtosecond laser is an ultrashort pulse width, which ensures that the heat-affected area is extremely small.

8. The femtosecond laser strengthening method for improving the surface integrity of laser cladding high-temperature alloy according to claim 7, characterized in that: The microstructure analysis uses an electron microscope to observe the interface between the cladding layer and the substrate and the changes in the grain structure; the hardness test uses a Vickers microhardness tester to measure the surface microhardness; and the residual stress test uses an X-ray diffraction non-destructive testing method to detect the surface residual stress.

Citation Information

Cited By

  • Wear-resistant alloy casting part for electric machinery and production process of wear-resistant alloy casting part

    CN120158690A